Comparison of cervical vertebral maturation and hand wrist skeletal maturation growth indicators in orthodontic patients - Litsas, George (My University, 2005)
Bu çalışmanın amacı lateral sefalometrik filmler üzerinde iki farklı yöntemle servikal vertebraların gelişimine bakılarak iskeletsel gelişimin değerlendirilmesi ve elde edilen sonuçların aynı bireylerin el-bilek filmlerine bakılarak tespit edilen iskeletsel gelişim durumlarıyla karşılaştırılmasıdır. Ki-kare testi, CVM metodu kullanılarak servikal vertebralardan elde edilen iskeletsel gelişim değerleri ile el-bilek filmlerinden elde edilen değerler arasında anlamlı bir korelasyon bulunduğunu göstermiştir (p<0.05). Servikal kemik yaşı ve el-bilek filmlerinden elde edilen iskelet yaşı arasında da yüksek bir korelasyon vardır (p<0.001). CVM evreleri ve el-bilek gelişim evrelerine tekabül eden kronolojik yaş gruplarında ise büyük değişkenlik gözlenmiştir. Comparison of cervical vertebral maturation and hand-wrist skeletal maturation as growth indicators in orthodontic patients

The purpose of this study was to predict skeletal maturation status based on the assessment of cervical vertebrae from lateral cephalometric radiographs according to two different methods, and to compare these findings with the skeletal maturity of the same individuals judged from the hand-wrist radiographs. The chi-square test showed that, skeletal maturational values obtained by the CVM method on cervical vertebrae were highly significant correlated with the skeletal values that were obtained from the hand-wrist analysis (p<0.05). The cervical bone age and the skeletal age based on the analysis of hand-wrist radiography were also highly correlated (p<0.001). There was great variability in the chronological age groups corresponding to both, the CVM stages and the hand-wrist maturation stages.
Keywords: bağ dokuları; eklemler; Hareket işlevleri ve deri; İnsan fizyolojisi; İskelet Gelişimi; Kemikler; Teknoloji (Uygulamalı bilimler); Tıp bilimleri